Fixed implant-retained rehabilitation of the edentulous maxilla: 11-year results of a prospective study - Mertens, Christian; Steveling, Helmut G.; Stucke, Kathrin; Pretzl, Bernadette; Bäumer, Amelie (Clinical implant dentistry and related research, 2012)
Objectives: The aim of the present study was to assess long-term survival and success rates of implants in the edentulous maxilla restored with an implant-supported fixed prosthesis. Materials and Methods: Seventeen edentulous patients received six to eight implants and implant-supported fixed prostheses by one surgeon. Yearly recalls were conducted by two examiners over a period of 11 years. Survival and success rates (biological complications) were determined; marginal bone loss was examined radiographically. Furthermore, microbiological tests as well as test for interleukin-1 composite genotype were assessed and potential risk factors were evaluated. Results: After a mean time of 11.26 years, 15 patients of 17 could be reexamined. Out of 94 implants, three were lost in one patient. Mean marginal bone loss reached 0.88 mm, two patients (at seven implants) showed bone loss of ≥3.2 mm. Survival rate of implants reached 96.8%. Success rates on implant level hit 92.6% according to the criteria of Albrektsson and colleagues and 83.0% in accordance with Karoussis and colleagues. One prosthesis had to be renewed. Conclusion: Within the limitation of this study, restoration of the edentulous maxilla with an implant-supported fixed prosthesis represents an effective tool for rehabilitation over a period of 11 years.
Gesehen am 29.11.2018